Chemical-induced variations in callus regenerated Atropa acuminata plants: A study on Ethyl Methanesulfonate effects - Shabeer Ahmad Dar; Ishfaq Shafi Khan; Gousia Majeed; Sumira Tyub; Irshad Ahmad Nawchoo; Azra Nahaid Kamili (Biotechnology Reports)
Atropa acuminata Royle ex Lindl. a member of the solanaceae family is a critically endangered medicinal herb indigenous to the Himalayan region of Kashmir and revered for its therapeutic and economic significance. Ethyl Methanesulfonate (EMS), a chemical mutagen, is commonly used to induce mutations for plant breeding and research purposes. In this study, callus cultures derived from leaf explants of A. acuminata were cultivated on Murashige and Skoog (MS) medium supplemented with Thidiazuron (0.1 mg/l) and treated with varying concentrations of EMS (0.1%, 1.0%) over defined time intervals. The impact of EMS concentrations and exposure durations, as well as their interactions, on the characteristics of regenerated callus were rigorously examined. The proliferation of shoots exhibited a diminishing trend with escalating EMS concentrations. Additionally, EMS elicited substantial alterations in the morphological and physiological attributes of the regenerated plants. Among the fifteen traits evaluated, mutant lines designated as M10, M11, and M6 displayed the most pronounced variations in morphological and physiological parameters compared to the control. Notably, the mutant line M10 exhibited significantly elevated shoot dry weight, root fresh weight, chlorophyll, and carotenoid contents demonstrating up to 98%, 31%, 348%, and 642% enhancements respectively as compared to the control. These mutant lines hold promise for further exploitation in augmenting physiological characteristics and enhancing the yield and quality of terpene glycosides in A. acuminata.